Transit-Oriented Development and the Implications for Equitable Development: A Case Study of the Milwaukee Streetcar - (:unkn) unknown (My University, 2019)
Many cities across the US have reintroduced the streetcar as an economic development tool, or as an image-branding and tourism-promoting amenity, while public transportation benefits are largely afterthoughts. The purpose of this research is to investigate the Milwaukee Streetcar as a transit-oriented development strategy, the distribution of benefits and burdens, and its implications for equitable development. Guided by semi-structured interviews and content/discourse analysis of planning/policy documents through an equity lens, this study analyzed Milwaukee’s initial downtown streetcar routes against the potential extension lines into the more transit-dependent communities of Bronzeville and Walker’s Point. The findings suggest that the initial routes and possible extension lines were engaged in very different political and planning processes, the latter of which employed explicit attention to equitable development. While certain tools have been identified to address concerns of displacement resulting from transit-oriented development, there continues to be several barriers to overcome to achieve equitable development.
Keywords: Community Development; Creative Cities; Equity; Regime Politics; Streetcar; Transit-Oriented Development